2016
DOI: 10.15252/embj.201592903
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP1 increases β‐cell regeneration by promoting α‐ to β‐cell transdifferentiation

Abstract: There is great interest in therapeutically harnessing endogenous regenerative mechanisms to increase the number of β cells in people with diabetes. By performing whole‐genome expression profiling of zebrafish islets, we identified 11 secreted proteins that are upregulated during β‐cell regeneration. We then tested the proteins' ability to potentiate β‐cell regeneration in zebrafish at supraphysiological levels. One protein, insulin‐like growth factor (Igf) binding‐protein 1 (Igfbp1), potently promoted β‐cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 62 publications
(95 reference statements)
1
69
0
Order By: Relevance
“…In this regard, our previous unbiased screens have identified enhancers of β-cell regeneration through different mechanisms; e.g. adenosine signaling promotes β-cell regeneration via increasing β-cell proliferation [2], whereas IGFBP1 promotes β-cell regeneration via increasing α-to-β-cell transdifferentiation [29]. Together, this line of research highlights the importance of performing unbiased screens for identification of potent endogenous pathways and mechanisms that can increase the number of β-cells, as well as translating initial phenotypic findings in discovery models to functional outcomes in mice and ultimately humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, our previous unbiased screens have identified enhancers of β-cell regeneration through different mechanisms; e.g. adenosine signaling promotes β-cell regeneration via increasing β-cell proliferation [2], whereas IGFBP1 promotes β-cell regeneration via increasing α-to-β-cell transdifferentiation [29]. Together, this line of research highlights the importance of performing unbiased screens for identification of potent endogenous pathways and mechanisms that can increase the number of β-cells, as well as translating initial phenotypic findings in discovery models to functional outcomes in mice and ultimately humans.…”
Section: Discussionmentioning
confidence: 99%
“…The following previously published transgenic zebrafish lines were used: Tg(ins:Flag-NTR) s950 [2], Tg(sst2:NTR,cryaa:Cerulean) KI102 [29] and Tg(ins:Venus-zGeminin; cryaa:Venus) KI107 [29]. We ablated β- or δ-cells in Tg(ins:Flag-NTR) or Tg(sst:NTR) zebrafish larvae by incubating the larvae in E3 supplemented with 10 mM metronidazole (MTZ; Sigma–Aldrich), 1% DMSO (VWR), and 0.2 mM 1-phenyl-2-thiourea (PTU; Acros Organics) from 3 to 4 days post fertilization (dpf).…”
Section: Methodsmentioning
confidence: 99%
“…The overexpression models Tg(tp1:cdk5rap1;cmlc2:eGFP) KI108 and Tg(tp1:cdkal1;cmlc2:eGFP) KI109 were generated by the Tol2 transposon system similarly to our previous report (3), with the following modifications. The constructs were generated by MultiSite Gateway cloning (Invitrogen) with forward primers 59-GGGGACAAGTTTGTACAAAAAAGCAG-GCTCTgccaccATGAACAGAATTAGTACTTTCA-39 for cdk5rap1 and 59-GGGGACAAGTTTGTACAAAAAAGCAGGCTCTgccacc-ATGATGGCGTTGGTGTGTG-39 for cdkal1, together with reverse primers 59-GGGGACCACTTTGTACAAGAAAGCT-GGGTCTCAGGCTGTTTTTCTGTCAT-39 for cdk5rap1 and 59-GGGGACCACTTTGTACAAGAAAGCTGGGTCTCAGAGC-AGTTTCTCCATC-39 for cdkal1 in the PCR, resulting in an amplicon for the BP reaction.…”
Section: Zebrafishmentioning
confidence: 99%
“…Apart from proliferation (1,2) and transdifferentiation (3)(4)(5), neogenesis (differentiation of new b-cells from endocrine progenitors or stem cells) is one of the major mechanisms in b-cell regeneration (6)(7)(8)(9)(10). Recent studies in mice have shown that pancreatic ductal ligation (PDL) or overexpression of the transcription factor Pax4 in a-cells induces neogenesis of endocrine cells originating from the pancreatic duct (8)(9)(10).…”
mentioning
confidence: 99%
“…b¡cell ablation or inhibition of insulin signaling alone induced a low level of islet cell transdifferentiation, 5,23,9,6 but this was enormously enhanced by PAR2 activation. 9 While we used a specific PAR2 agonist rather than relatively nonspecific proteases to activate PAR2, it should be noted that trypsin-like proteases are widely expressed, including in b¡cells.…”
Section: Discussionmentioning
confidence: 99%